Botulinum toxin versus others alternative methods as an option for the management of patients with bruxism: Systematic review (Research, Society and Development, 2022)
Objective: To determine if botulinum toxin is effective as a treatment for adult patients diagnosed with bruxism according to RCT-type scientific articles that have been published from 2016 to 2021. Methodology: An electronic search was carried out between November 2021 and January 2022 through three digital databases (PubMed, Science Direct, Cochrane Library), using the keywords "Bruxism", "¨Teeth grinding", "Botulinum toxin" , “Botox”, “Botulinum toxin A”, “Botulinum toxin type A” combined through the Boolean equation “AND”. For this review, the PRISMA scientific tool was considered, articles published in the last 5 years, in English and Spanish, in adult patients with bruxism, RCT type and prospective comparing Botox with placebo or traditional methods were included. Results: Of 90 screened articles, 6 RCTs were included in the review. Of these, 3 studies compared the effectiveness of BTX with occlusal splints and the remaining 3 with placebo. No significant differences were found between both methods and a decrease in symptoms and episodes of bruxism was observed. Control sessions were carried out up to 12 months without reporting adverse effects. Conclusions: BTX and traditional methods are appropriate for the treatment of bruxism because they reduce symptoms and prevent the appearance or progression of clinical signs. Nevertheless; considering that the pathology is multifactorial, the ideal treatment should be multidisciplinary, including: psychological and neurological treatment, physical therapy, pharmacological treatment, BTX applications combined with occlusal splints and restorative treatments.